Development of an RSM-based predictive model for evaluation of corrosion efficiency of ATMP in one molar HCl for carbon steel samples - Ahmadi, Soroush; Khormali, Azizollah (Petroleum science and technology, 2024)
The corrosion control of carbon steel was investigated using ATMP (amino-trimethylene-phosphonic acid) by experimental weight loss and response surface methods. For this purpose, the simultaneous effect of the important parameters, including inhibitor concentration, temperature, and exposure time on the inhibition efficiency (IE) of ATMP was evaluated. A new RSM-based model was developed to predict ATMP effectiveness. The results obtained from Fit-statistics (R 2 = 0.9946, Adj-R 2 = 0.9916, and Pred-R 2 = 0.9750), adequate precision (A.p = 63.1026), diagnostics plots, and PPE (Percentage-Prediction-Error) for non-designed experiments strongly confirmed the adequacy, accuracy, and validation of the developed IE-model. The results indicated that the parameters at the low levels of ATMP concentrations had the least interaction effect on the inhibition efficiency (IE< 35%). The addition of inhibitor concentration up to 150 ppm near the low level of temperature (30-40 °C) and high level of exposure time (85-105 h) had the most interaction effect between parameters and significantly enhanced the inhibition efficiency. Furthermore, numerical optimization was performed to maximize IE while minimizing the concentration of inhibitor. The optimization provided showed an inhibition performance of 80.434% at 126 ppm, 31 °C, and 26.4 h.